Enhancing the Efficiency of Securities Markets in East Asia - Ghosh, Swati (World Bank, Washington, DC, 2012)
The authors explore the relative efficiency of stock markets across countries using newly available data on transactions costs and the quality of the informational environment of stock markets. These new measures are constructed from firm-level stock returns in a panel of 60 countries for the period 2000-04. The authors then develop a framework to understand the linkages between efficiency, liquidity, and their determinants. To give empirical content to the framework, they study the determinants of transactions costs and the quality of the informational environment. They find that some institutional arrangements-such as the availability of stock lending and short selling-and the openness of markets are associated with lower transactions costs. The authors also find that, although disclosure rules for directors and officers of listed firms are essential, the ability of shareholders to seek redress is more conducive to a better informational environment in stock markets. This in turn serves as the basis for the policy framework and recommendations for the East Asian region. In particular, the region needs to continue to strengthen the implementation and enforcement of corporate governance, to further enhance the market and institutional infrastructure, and focus on policy measures to foster a larger and more diversified investor base to continue to see gains in the efficiency of stock markets.